THE IMPACT OF MARKETING MANAGEMENT ON MARKET COMPETITION FOR SMALL COMPANIES IN BASRA MARKET COMPETITION - Ali Khalaf Mohammed Al Sukaini (Scholar Express Journals, 2022)
The research investigates1.The various aspects that influence marketing management in small industrial and commercial businesses in Basra, Iraq.2. Investigate the various formats, degrees of execution, and marketing strategies used in Basra, Iraq.3. Investigate the relationship between marketing management and marketing success in Basra, Iraq.This research used a quantitative research design, which is defined as the measurement and statistical, mathematical, or numerical analysis of data collected through interviews, questionnaires, and observations.This study using the method of questionnaire and interviews data were collected from the residents of Basra city in Iraq and after the data was collected the study was conducted on a sample of 30 small companies in Basra, Iraq. The application of the research tool 'Questionnaire' in a set of questions for a sample of (30) individuals, the results were as follows. Was your business plan successful in attracting customers? The number of yes answers (19) and no answers (11) at a rate of 63.3%. And the fourth question about the distribution of leaflets promoting the product, the answer was yes (25) and the answers were no (5)
Keywords: marketing management; market competition; Basra Market competition